Co-oscillation and synchronization between the posterior thalamus and the caudate nucleus during visual stimulation - Gombkötő, P.; Berényi, A.; Nagypál, T.; Benedek, G.; Braunitzer, G.; Nagy, A. (Neuroscience, 2013)
•CN–SG local field potential pairs were recorded and analyzed.•Our results suggest bidirectional information flow between the CN and the SG.•Co-oscillation was found during visual stimulation between the CN and the posterior thalamus.•Static stimulation increased the cross-correlation of the beta frequency components.•Dynamic visual stimulation was reflected by changes in the theta frequency signal. Recent results suggest significant cross-correlation between the spike trains of the suprageniculate nucleus (SG) of the posterior thalamus and the caudate nucleus (CN) during visual stimulation. In the present study visually evoked local field potentials (LFPs) were recorded simultaneously in the CN and the SG in order to investigate the coupling between these structures at a population level. The effect of static and dynamic visual stimulation was analyzed in 55 SG–CN LFP pairs in the frequency range 5–57Hz. Statistical analysis revealed significant correlation of the relative powers of each investigated frequency band (5–8Hz, 8–12Hz, 12–35Hz and 35–57Hz) during both static and dynamic visual stimulation. The temporal evolution of cross-correlation showed that in the majority of the cases the SG was activated first, and in approximately one third of the cases, the CN was activated earlier. These observations suggest a bidirectional information flow. The most interesting finding of this study is that different frequency bands exhibited significant cross-correlation in a stimulation paradigm-dependent manner. That is, static stimulation usually increased the cross-correlation of the higher frequency components (12–57Hz) of the LFP, while dynamic stimulation induced changes in the lowest frequency band (5–8Hz). This suggests a parallel processing of dynamic and static visual information in the SG and the CN. To our knowledge we are the first to provide evidence on the co-oscillation and synchronization of the CN and the SG at a population level upon visual stimulation, which suggests a significant cooperation between these structures in visual information processing.